Repurposing BCL-2 and Jak 1/2 inhibitors: Cure and treatment of HIV-1 and other viral infections - Reece, Monica D.; Song, Colin; Hancock, Sarah C.; Pereira Ribeiro, Susan; Kulpa, Deanna A.; Gavegnano, Christina (Frontiers in Immunology, 2022)
B cell lymphoma 2 (BCL-2) family proteins are involved in the mitochondrial apoptotic pathway and are key modulators of cellular lifespan, which is dysregulated during human immunodeficiency virus type 1 (HIV-1) and other viral infections, thereby increasing the lifespan of cells harboring virus, including the latent HIV-1 reservoir. Long-lived cells harboring integrated HIV-1 DNA is a major barrier to eradication. Strategies reducing the lifespan of reservoir cells could significantly impact the field of cure research, while also providing insight into immunomodulatory strategies that can crosstalk to other viral infections. Venetoclax is a first-in-class orally bioavailable BCL-2 homology 3 (BH3) mimetic that recently received Food and Drug Administration (FDA) approval for treatment in myeloid and lymphocytic leukemia. Venetoclax has been recently investigated in HIV-1 and demonstrated anti-HIV-1 effects including a reduction in reservoir size. Another immunomodulatory strategy towards reduction in the lifespan of the reservoir is Jak 1/2 inhibition. The Jak STAT pathway has been implicated in BCL-2 and interleukin 10 (IL-10) expression, leading to a downstream effect of cellular senescence. Ruxolitinib and baricitinib are FDA-approved, orally bioavailable Jak 1/2 inhibitors that have been shown to indirectly decay the HIV-1 latent reservoir, and down-regulate markers of HIV-1 persistence, immune dysregulation and reservoir lifespan in vitro and ex vivo. Ruxolitinib recently demonstrated a significant decrease in BCL-2 expression in a human study of virally suppressed people living with HIV (PWH), and baricitinib recently received emergency use approval for the indication of coronavirus disease 2019 (COVID-19), underscoring their safety and efficacy in the viral infection setting. BCL-2 and Jak 1/2 inhibitors could be repurposed as immunomodulators for not only HIV-1 and COVID-19, but other viruses that upregulate BCL-2 anti-apoptotic proteins. This review examines potential routes for BCL-2 and Jak 1/2 inhibitors as immunomodulators for treatment and cure of HIV-1 and other viral infections.